Of mice and men: is there a future for metformin in the treatment of hepatic steatosis? - Green, C; Marjot, T; Tomlinson, J; Hodson, L (Wiley, 2018)
Non-alcoholic fatty liver disease (NAFLD) encompasses a spectrum of liver diseases, of which the first stage is steatosis. It is one of the most common liver diseases in developed countries and there is a clear association between type 2 diabetes (T2DM) and NAFLD. It is estimated that 70% of people with T2DM have NAFLD and yet there is currently no licensed pharmacological agent to treat it. Whilst lifestyle modification may ameliorate liver fat, it is often difficult to achieve or sustain; thus, there is great interest in pharmacological treatments for NAFLD. Metformin is the first-line medication in the management of T2DM and evidence from animal and human studies has suggested that it may be useful in reducing liver fat via inhibition of lipogenesis and increased fatty acid oxidation. Findings from the majority of studies undertaken in rodent models clearly suggest that metformin may be a powerful therapeutic agent specifically to reduce liver fat accumulation; data from human studies are less convincing. In the present review we discuss the evidence for the specific effects of metformin treatment on liver fat accumulation in animal and human studies, as well as the underlying proposed mechanisms, to try and understand and reconcile the difference in findings between rodent and human work in this area.